LANGUAGE STYLE USED IN THE SLOGANS OF SAMPOERNA ADVERTISEMENTS - ERNESTIVITA, GESTY (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords: Language style, language style based on lexicon, language style based on sentence structure, Sampoerna.   When delivering ideas through language, people may use different language variety that is called style. “People use a different language style when they are communicating with others because from the style they can recognize the speaker’s background and the reason of using a variety of language that he/she uses” (Trudgill, 2002:2). In conducting the study, the writer analyzed two problems of study namely; (1) What kinds of language style used in the slogans of Sampoerna advertisements seen from its lexicon (2) What kinds of language style used in the slogans of Sampoerna advertisements seen from its sentence structure. The main theory used in this study is the language style theory proposed by Keraf Gorys (2010) supported by theories proposed by Trudgill& Pratt (1980) and Abdul Chaer (2006). This study used qualitative and document analysis since the analysis focused on analyzing and interpreting the text in the form of slogans. The data of this study were the slogans of Sampoerna advertisements taken from internet and some from other sources like television and newspapers. In this study, the writer described the data by using tables. The writer revealed that language style based on lexicon of both formal and informal are found. Moreover, in this study the writer included the characteristics of lexical and grammatical of Bahasa Indonesia which can be seen in appendices. It was done in order to make deeper analysis. The language style based on sentence structure (climax, anticlimax, parallelism, antithesis, and repetition) was found in this study. However, the writer only found four styles because parallel style is not found in the data. From 20 slogans analyzed based on lexicon, the writer found out that there were seven slogans categorized into formal language style and there are 13 slogans categorized into informal language style. Based on sentence structure, from 20 slogans, it was found out that there are 11 slogans of climax, four slogans is anticlimax, one slogan is antithesis and four slogans is repetition. Last, the writer suggests for the future study to analyze language style that occurs in the slogan of Indonesian advertisement not only from its lexicon and sentence structure but maybe can also be seen from its meaning because it will contribute deeper analysis.